Jogos de linguagem e reflexividade em Heráclito de Éfeso. - Martim Reyes da Costa Silva (2021)
Throughout the approximately two thousand and five hundred years that separate us from the time when it was composed, as we can see from ancient testimonies, the text of Heraclitus of Ephesus has been the object of many different interpretations. Despite their diversity, however, most of them have recognized both the poetic quality of the composition and the philosophical potentiality of the heraclitean reflections. Considering these two dimensions of the text, this study turns to its interconnection between form and content, between language play and reflexivity. Thinking the text as a whole and its relation to its historical context, it is pointed out how, by criticizing the great references and resemantizing fundamental notions of the intellectual culture of his time, the Ephesian presents himself as a competitor in the art of the word, in a discourse that reaffirms the unity of all things as a reality at the same time inescapable and indecipherable, denouncing human alienation but also defending and inducing the audience to a reflective exercise. In this way, the language games are articulated with the content of the discourse, creating a network of semantic resonances that suggests a continuous and dynamic reinterpretation of meanings. The "concision and gravity" of his style, as defined by Diogenes Laertius (Book IX, 5-9), in this regard, are understood as part of a semantic density, which interweaves a considerable range of poetic resources into a philosophical provocation about language itself - but also about thought and the real. In particular, the importance of reflection on language and how it expands from the metaphors of speaking and listening is highlighted here. Understood as a synthetic (from the notion of lógos, the "word") and interpretative (from the notion of listening) exercise, language shows itself as an ambiguous instrument, but also as a path to a human wisdom, which is characterized by the exercise of reflexivity.